High-strength and high-conductivity copper-aluminum-copper composite material and preparation process thereof

Through the design and process of copper-aluminum-copper composite materials with multi-layer structure, the problem of poor weight reduction effect caused by excessive thickness of existing copper-aluminum composite materials is solved, and the effects of high tensile strength, conductivity and weight reduction are achieved.

CN119526847AActive Publication Date: 2025-02-28JIANGSU ZHONGSE COMPOSITE MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411675490.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-28
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

When existing copper-aluminum composite materials reach high tensile strength, the thickness of the copper layer accounts for too much, resulting in poor weight reduction effect, affecting its promotion in high strength and high conductivity.

Method used

The copper-aluminum-copper composite material design adopts a multi-layer structure, including the first high-strength copper alloy layer, the first aluminum layer, the second aluminum layer, the third aluminum layer and the second high-strength copper alloy layer. By controlling the thickness and material combination of each layer, combining continuous casting and hot-rolling composite processes, the strength and conductivity of the composite material are improved.

Benefits of technology

High tensile strength (not less than 360MPa) and high conductivity (not less than 70% IACS) are achieved. At the same time, by optimizing the layer structure and process, the material density is reduced and the weight reduction effect is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119526847A_ABST
    Figure CN119526847A_ABST
Patent Text Reader

Abstract

The invention aims to disclose a high-strength and high-conductivity copper-aluminum-copper composite material and a preparation process thereof, and relates to the technical field of metal composites.The copper-aluminum-copper composite material sequentially comprises a first high-strength copper alloy layer, a first aluminum layer, a second aluminum layer, a third aluminum layer and a second high-strength copper alloy layer from top to bottom; the ratio of the thickness of the first high-strength copper alloy layer to the thickness of the first aluminum layer to the thickness of the second aluminum layer to the thickness of the third aluminum layer to the thickness of the second high-strength copper alloy layer is (0.2-0.3): (0.05-0.07): (0.5-0.7): (0.05-0.07): (0.2-0.3); the cast-rolling composite aluminum alloy plate has the beneficial effects that the first aluminum layer and the third aluminum layer are both made of 8011 aluminum alloy or 1060 aluminum alloy, the first aluminum layer and the first high-strength copper alloy layer have high wettability, and the cast-rolling composite strength is high; the second aluminum layer is made of 7A52 aluminum alloy or 6013 aluminum alloy, has the characteristics of light weight and high strength, and is compounded between the first aluminum layer and the third aluminum layer through hot rolling, so that a high-strength composite interface is formed among the first aluminum layer, the second aluminum layer and the third aluminum layer, and the high-strength and high-conductivity copper-aluminum-copper composite material is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal composite materials, and in particular to a high-strength and high-conductivity copper-aluminum-copper composite material and a preparation process thereof. Background Art

[0002] In the fields of aerospace, transportation, electronic communications, marine engineering, special equipment, etc., high strength and high conductivity are required for conductor materials, and copper-aluminum composite materials are one of the good choices.

[0003] At present, in order for the tensile strength of copper-aluminum composite materials to reach the requirement of 350MPa, the thickness of the copper layer needs to account for more than 50%. This makes the copper layer account for too large a proportion, and the weight reduction effect is general, which affects the promotion of high-strength and high-conductivity copper-aluminum-copper composite materials.

[0004] In view of this, it is necessary to develop a high-strength and high-conductivity copper-aluminum-copper composite material and its preparation process to overcome the above-mentioned defects. Summary of the invention

[0005] The purpose of the invention is to disclose a high-strength and high-conductivity copper-aluminum-copper composite material and a preparation process thereof.

[0006] The first object of the present invention is to provide a high-strength and high-conductivity copper-aluminum-copper composite material.

[0007] The second object of the present invention is to provide a process for preparing a high-strength and high-conductivity copper-aluminum-copper composite material.

[0008] To achieve the above-mentioned first invention objective, the present invention provides a high-strength and high-conductivity copper-aluminum-copper composite material, the copper-aluminum-copper composite material comprises, from top to bottom, a first high-strength copper alloy layer, a first aluminum layer, a second aluminum layer, a third aluminum layer and a second high-strength copper alloy layer, the thickness of the first high-strength copper alloy layer: the thickness of the first aluminum layer: the thickness of the second aluminum layer: the thickness of the third aluminum layer: the thickness of the second high-strength copper alloy layer is (0.2-0.3): (0.05-0.07): (0.5-0.7): (0.05-0.07): (0.2-0.3);

[0009] The first high-strength copper alloy layer is T2 copper alloy or C18150 copper alloy;

[0010] The first aluminum layer and the third aluminum layer are made of 8011 aluminum alloy or 1060 aluminum alloy;

[0011] The second aluminum layer is made of 7A52 aluminum alloy or 6013 aluminum alloy.

[0012] Preferably, the tensile strength of the copper-aluminum-copper composite material is not less than 360 MPa, and the electrical conductivity of the copper-aluminum-copper composite material is not less than 70% IACS.

[0013] Based on the same inventive principle, in order to achieve the above first inventive object, the present invention provides a process for preparing a high-strength and high-conductivity copper-aluminum-copper composite material, comprising the following steps:

[0014] Heating a high-strength copper alloy strip to a first temperature, wherein the first temperature is 100° C. to 150° C., and the high-strength copper alloy strip is a T2 copper alloy or a C18150 copper alloy;

[0015] The first aluminum alloy is liquefied and heated to a second temperature to obtain a liquid first aluminum alloy, wherein the second temperature is 30° C. to 60° C. higher than the melting point of the first aluminum alloy, and the first aluminum alloy is made of 8011 aluminum alloy or 1060 aluminum alloy;

[0016] The liquid first aluminum alloy and the high-strength copper alloy strip are continuously cast and rolled, and the high-strength copper alloy strip is heated from the first temperature to a third temperature, and the third temperature is 30° C. to 60° C. higher than the unit cell transformation temperature of the high-strength copper alloy strip, to obtain a copper-aluminum composite substrate;

[0017] The copper-aluminum composite substrate is simultaneously hot-rolled on both sides of a high-strength aluminum alloy strip to obtain a copper-aluminum-copper composite material. The material of the high-strength aluminum alloy strip is 7A52 aluminum alloy or 6013 aluminum alloy.

[0018] Preferably, the speed of the continuous casting is 0.5 m / s-3 m / s.

[0019] Preferably, the speed of the continuous casting is 1 m / s-2 m / s.

[0020] Preferably, the rolling force of the continuous casting is 1000t-2000t.

[0021] Preferably, the composite temperature of the hot rolling composite is 480° C.-520° C., and the rolling force of the hot rolling composite is 100 t-1200 t.

[0022] Preferably, the pressing rate of the hot rolling composite is 10%-20%.

[0023] Preferably, the tensile strength of the copper-aluminum-copper composite material is not less than 360 MPa, and the electrical conductivity of the copper-aluminum-copper composite material is not less than 70% IACS.

[0024] Preferably, the high-strength aluminum alloy strip and the two layers of the composite copper-aluminum composite substrate are synchronously sent to a layer temperature control furnace, and the layer temperature control furnace is provided with a protective atmosphere, wherein the protective atmosphere comprises 20%-30% hydrogen and the rest is nitrogen.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The first aluminum layer and the third aluminum layer of the present invention are made of 8011 aluminum alloy or 1060 aluminum alloy, which has high wettability with the first high-strength copper alloy layer and high cast-rolling composite strength; the second aluminum layer is made of 7A52 aluminum alloy or 6013 aluminum alloy, which has the characteristics of light weight but high strength, and is hot-rolled and composited between the first aluminum layer and the third aluminum layer, so that a high-strength composite interface is formed between the first aluminum layer, the second aluminum layer and the third aluminum layer, forming a high-strength and high-conductivity copper-aluminum-copper composite material, whose tensile strength is not less than 360 MPa and electrical conductivity is not less than 70% IACS.

[0027] (2) The first aluminum layer and the third aluminum layer of the present invention contain Si. The function of Si is to increase the wettability between aluminum and copper, ensure the wettability between the high-wettability aluminum alloy liquid and the high-strength copper alloy strip, and increase the peeling force between the copper-aluminum composite material. The first temperature is the initial temperature of the high-strength copper alloy strip. When the liquid first aluminum alloy and the high-strength copper alloy strip having the first temperature are continuously cast and rolled, the heat of the liquid first aluminum alloy will be transferred and diffused to the high-strength copper alloy strip, and the temperature of the high-strength copper alloy strip will reach the third temperature. The third temperature is 30°C-60°C higher than the unit cell transformation temperature of the high-strength copper alloy strip. By controlling the first temperature, the second temperature and the third temperature, the composite strength between the copper-aluminum composite material is further increased. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a cross-sectional view of the high-strength and high-conductivity copper-aluminum-copper composite material of the present invention.

[0029] Figure 2 It is a process flow chart of the preparation of the high-strength and high-conductivity copper-aluminum-copper composite material of the present invention.

[0030] Figure 3 It is an electron microscope image of the copper-aluminum casting and rolling interface of the present invention.

[0031] Figure 4 It is an element line scan diagram of the copper-aluminum casting and rolling interface of the present invention.

[0032] Figure 5 This is an electron microscope image of the interface between the first aluminum layer and the second aluminum layer of the present invention.

[0033] Among them, 1. the first high-strength copper alloy layer; 2. the first aluminum layer; 3. the second aluminum layer; 4. the third aluminum layer; 5. the second high-strength copper alloy layer. DETAILED DESCRIPTION

[0034] The present invention is described in detail below in conjunction with the various embodiments shown in the accompanying drawings, but it should be noted that these embodiments are not limitations of the present invention, and any equivalent transformations or substitutions in functions, methods, or structures made by ordinary technicians in the field based on these embodiments are all within the scope of protection of the present invention.

[0035] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thick", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate directions or positional relationships based on the directions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific direction, be constructed and operated in a specific direction, and therefore should not be understood as limiting the present invention.

[0036] Embodiment 1

[0037] See also Figure 1 The present embodiment provides a high-strength and high-conductivity copper-aluminum-copper composite material, which comprises, from top to bottom, a first high-strength copper alloy layer 1, a first aluminum layer 2, a second aluminum layer 3, a third aluminum layer 4 and a second high-strength copper alloy layer 5, wherein the thickness of the first high-strength copper alloy layer 1: the thickness of the first aluminum layer 2: the thickness of the second aluminum layer 3: the thickness of the third aluminum layer 4: the thickness of the second high-strength copper alloy layer 5 is (0.2-0.3): (0.05-0.07): (0.5-0.7): (0.05-0.07): (0.2-0.3); the first high-strength copper alloy layer 1 is T2 copper alloy or C18150 copper alloy; the materials of the first aluminum layer 2 and the third aluminum layer 4 are both 8011 aluminum alloy or 1060 aluminum alloy; the material of the second aluminum layer 3 is 7A52 aluminum alloy or 6013 aluminum alloy.

[0038] Specifically, see Figure 1 The thickness of the first high-strength copper alloy layer 1: the thickness of the first aluminum layer 2: the thickness of the second aluminum layer 3: the thickness of the third aluminum layer 4: the thickness of the second high-strength copper alloy layer 5 is preferably 0.2: 0.05: 0.7: 0.05: 0.2, the sum of the thickness of the first high-strength copper alloy layer 1 and the second high-strength copper alloy layer 5 accounts for 33.3% of the total thickness of the copper-aluminum-copper composite material, the sum of the thickness of the first aluminum layer 2, the second aluminum layer 3, and the third aluminum layer 4 accounts for 66.7% of the total thickness, under this thickness ratio, the tensile strength of the copper-aluminum-copper composite material is not less than 360MPa, and the electrical conductivity of the copper-aluminum-copper composite material is not less than 70%IACS, achieving high strength and high conductivity, and at the same time the density of the copper-aluminum-copper composite material is greatly reduced compared to pure copper, achieving a significant weight reduction.

[0039] Embodiment 2

[0040] See also Figure 1 , a high-strength and high-conductivity copper-aluminum-copper composite material preparation process, comprising the following steps:

[0041] S1: heating the high-strength copper alloy strip to a first temperature, the first temperature is 100°C-150°C, and the high-strength copper alloy strip is T2 copper alloy or C18150 copper alloy. Specifically, the first temperature is the initial temperature of the high-strength copper alloy strip, and the first temperature is preferably 130°C. The initial temperature can ensure that the composite temperature with the first aluminum alloy during subsequent continuous rolling meets the requirements, thereby ensuring the composite strength; the high-strength copper alloy strip is heated to the first temperature by the copper strip auxiliary heating device, that is, the high-strength copper alloy strip is heated to the first temperature after passing through the auxiliary heating device.

[0042] S2: liquefy the first aluminum alloy and heat it to a second temperature to obtain a liquid first aluminum alloy, wherein the second temperature is 30°C-60°C higher than the melting point of the first aluminum alloy, and the material of the first aluminum alloy is 8011 aluminum alloy or 1060 aluminum alloy. Specifically, the role of Si in the first aluminum alloy is to increase the wettability between aluminum and copper, ensure the wettability between the first aluminum alloy and the high-strength copper alloy strip, and increase the composite strength between the copper-aluminum composite material; in addition, the second temperature is 30°C-60°C higher than the melting point of the first aluminum alloy, and the second temperature is preferably 35°C higher than the melting point of the first aluminum alloy, so that the first aluminum alloy carries enough heat.

[0043] S3: Continuously casting and rolling the liquid first aluminum alloy and the high-strength copper alloy strip, wherein the high-strength copper alloy strip is heat-transferred from the first temperature to a third temperature, wherein the third temperature is 30°C-60°C higher than the unit cell transformation temperature of the high-strength copper alloy strip, to obtain a copper-aluminum composite substrate. Specifically, the liquid first aluminum alloy is transported to the casting and rolling area through the guide groove and the casting nozzle, and the first aluminum alloy is used to ensure high wettability between copper and aluminum; the speed of the continuous casting and rolling is 0.5m / s-3m / s, and the speed of the continuous casting and rolling is preferably 1m / s-2m / s. The rolling force of the continuous casting and rolling is 1000t-2000t, and the rolling force is preferably 2000t; to further ensure the composite strength between copper and aluminum, the first temperature is the initial temperature of the high-strength copper alloy strip, and the first temperature is preferably 130°C. When the first aluminum alloy and the high-strength copper alloy strip having the first temperature are continuously cast and rolled, the heat of the first aluminum alloy will be transferred and diffused to the high-strength copper alloy strip, and the temperature of the high-strength copper alloy strip reaches the third temperature, and the third temperature is 30°C-60°C higher than the unit cell transformation temperature of the high-strength copper alloy strip, the unit cell transformation temperature is preferably 400°C, and the third temperature is preferably 430°C. By controlling the first temperature, the second temperature and the third temperature, the composite strength between the copper-aluminum composite materials is further increased.

[0044] S4: Synchronously hot-roll a copper-aluminum composite substrate on both sides of a high-strength aluminum alloy strip to obtain a copper-aluminum-copper composite material, wherein the material of the high-strength aluminum alloy strip is 7A52 aluminum alloy or 6013 aluminum alloy. Specifically, the composite temperature of the hot-rolling composite is 480°C-520°C, preferably 500°C, the rolling force of the hot-rolling composite is 100t-1200t, preferably 1000t, the pressing rate of the hot-rolling composite is 10%-20%, and the pressing rate is preferably 15%; 7A52 aluminum alloy or 6013 aluminum alloy has the characteristics of light weight and high strength, 7A52 aluminum alloy or 6013 aluminum alloy contains more zinc components, and the wettability between 7A52 aluminum alloy or 6013 aluminum alloy and high-strength copper alloy strip is poor, making it difficult to directly composite them together or the composite strength cannot be In order to meet the use requirements, in this embodiment, a first aluminum alloy is compounded between the high-strength aluminum alloy strip and the high-strength copper alloy strip. The first aluminum alloy has good wettability with the high-strength aluminum alloy strip. The main components of the first aluminum alloy and the high-strength aluminum alloy strip are both aluminum, and the first aluminum alloy and the high-strength aluminum alloy strip have better wettability. In this embodiment, a high-strength and high-conductivity composite material is prepared by a process of continuous casting and hot rolling composite, so that the tensile strength of the copper-aluminum-copper composite material is not less than 360MPa, and the electrical conductivity of the copper-aluminum-copper composite material is not less than 70%IACS.

[0045] It should be noted that before hot rolling and cladding, the high-strength aluminum alloy strip and the two layers of the composite copper-aluminum composite substrate are synchronously sent to a layer temperature control furnace, and the layer temperature control furnace is provided with a protective atmosphere, and the protective atmosphere includes 20%-30% hydrogen and the rest is nitrogen. The protective atmosphere ensures the brightness of the high-strength aluminum alloy strip and the two layers of the composite copper-aluminum composite substrate, prevents them from oxidation, and provides a basis for ensuring the quality of the composite interface.

[0046] Through steps S1 to S4, the high-strength and high-conductivity copper-aluminum-copper composite material described in Example 1 is prepared. The tensile strength of the copper-aluminum-copper composite material is not less than 360 MPa, and the electrical conductivity of the copper-aluminum-copper composite material is not less than 70% IACS. The interface electron microscope image between the first high-strength copper alloy layer 1 (C18150 copper alloy) and the first aluminum layer 2 (1060 aluminum alloy) is shown in FIG. Figure 3 It can be seen that the interface of the composite material prepared by casting and rolling is flat and well bonded. The SEM morphology of the composite material of the first high-strength copper alloy layer 1 and the first aluminum layer 2 shows that there are no obvious holes and impurity defects at the interface, the Cockendall effect produced by diffusion is weak, and an interface layer of about 0.8μm is produced. The interface line on both sides of copper and aluminum is smooth, and the metallurgical state is good, which is conducive to the subsequent rolling processing and heat treatment; see Figure 4 , Figure 4 It is the element line scan display. Figure 3 The atomic ratio of aluminum atoms to copper atoms at point 1 is close to 4:9. Figure 3The atomic ratio of aluminum atoms to copper atoms at point 2 is close to 2:1. From the copper side to the aluminum side, the copper content gradually decreases while the aluminum content is the opposite. Based on the above analysis, it can be determined that the interface is divided into two layers. The interface layer close to copper is Al4Cu9 interface compound, and the interface layer close to aluminum is Al2Cu interface compound; see Figure 5 , Figure 5 This is an electron microscope image of the interface between the first aluminum layer 2 and the second aluminum layer 3. The first aluminum layer 2 is based on 1060 aluminum alloy, and the second aluminum layer 3 is based on 7A52 aluminum alloy. Figure 5 It shows that there is no obvious interface between the first aluminum layer 2 and the second aluminum layer 3, indicating that the first aluminum layer 2 and the second aluminum layer 3 are firmly bonded.

[0047] See Table 1, which is a performance parameter table of the copper-aluminum composite material.

[0048] Table 1 Performance parameters of copper-aluminum composite materials

[0049]

[0050] From the test results in Table 1, it can be seen that the influence on the tensile strength MPa, electrical conductivity and other aspects of the copper-aluminum composite material is mainly reflected in the following aspects: (1) The first temperature is the key factor. The second temperature and the first temperature combine to ensure the third temperature, thereby ensuring the composite interface and tensile strength; (2) The rolling force plays an auxiliary role in the tensile strength MPa; (3) The tensile strength MPa, electrical conductivity and other aspects of the copper alloy and aluminum alloy models provide basic guarantees.

Claims

1. High-strength and high-conductivity copper-aluminum-copper composite material, characterized in that: The copper-aluminum-copper composite material includes, from top to bottom, a first high-strength copper alloy layer, a first aluminum layer, a second aluminum layer, a third aluminum layer and a second high-strength copper alloy layer, wherein the thickness of the first high-strength copper alloy layer is: the thickness of the first aluminum layer is: the thickness of the second aluminum layer is: the thickness of the third aluminum layer is: the thickness of the second high-strength copper alloy layer is (0.2-0.3): (0.05-0.07): (0.5-0.7): (0.05-0.07): (0.2-0.3); The first high-strength copper alloy layer is T2 copper alloy or C18150 copper alloy; The first aluminum layer and the third aluminum layer are made of 8011 aluminum alloy or 1060 aluminum alloy; The second aluminum layer is made of 7A52 aluminum alloy or 6013 aluminum alloy.

2. The high-strength and high-conductivity copper-aluminum-copper composite material according to claim 1, characterized in that: The tensile strength of the copper-aluminum-copper composite material is not less than 360 MPa, and the electrical conductivity of the copper-aluminum-copper composite material is not less than 70% IACS.

3. A process for preparing a high-strength and high-conductivity copper-aluminum-copper composite material, characterized in that: The following steps are involved: Heating a high-strength copper alloy strip to a first temperature, wherein the first temperature is 100° C. to 150° C., and the high-strength copper alloy strip is a T2 copper alloy or a C18150 copper alloy; The first aluminum alloy is liquefied and heated to a second temperature to obtain a liquid first aluminum alloy, wherein the second temperature is 30° C. to 60° C. higher than the melting point of the first aluminum alloy, and the first aluminum alloy is made of 8011 aluminum alloy or 1060 aluminum alloy; The liquid first aluminum alloy and the high-strength copper alloy strip are continuously cast and rolled, and the high-strength copper alloy strip is heated from the first temperature to a third temperature, and the third temperature is 30° C. to 60° C. higher than the unit cell transformation temperature of the high-strength copper alloy strip, to obtain a copper-aluminum composite substrate; The copper-aluminum composite substrate is simultaneously hot-rolled on both sides of a high-strength aluminum alloy strip to obtain a copper-aluminum-copper composite material. The material of the high-strength aluminum alloy strip is 7A52 aluminum alloy or 6013 aluminum alloy.

4. The process for preparing the high-strength and high-conductivity copper-aluminum-copper composite material according to claim 3, characterized in that: The speed of the continuous casting is 0.5m / s-3m / s.

5. The process for preparing the high-strength and high-conductivity copper-aluminum-copper composite material according to claim 4, characterized in that: The speed of the continuous casting is 1m / s-2m / s.

6. The process for preparing the high-strength and high-conductivity copper-aluminum-copper composite material according to claim 3, characterized in that: The rolling force of the continuous casting and rolling is 1000t-2000t.

7. The process for preparing the high-strength and high-conductivity copper-aluminum-copper composite material according to claim 3, characterized in that: The composite temperature of the hot rolling composite is 480° C.-520° C., and the rolling force of the hot rolling composite is 100t-1200t.

8. The process for preparing the high-strength and high-conductivity copper-aluminum-copper composite material according to claim 7, characterized in that: The pressing rate of the hot rolling composite is 10%-20%.

9. The process for preparing the high-strength and high-conductivity copper-aluminum-copper composite material according to claim 3, characterized in that: The tensile strength of the copper-aluminum-copper composite material is not less than 360 MPa, and the electrical conductivity of the copper-aluminum-copper composite material is not less than 70% IACS.

10. The process for preparing the high-strength and high-conductivity copper-aluminum-copper composite material according to claim 3, characterized in that: The high-strength aluminum alloy strip and the two layers of the composite copper-aluminum composite substrate are synchronously sent to a layer temperature control furnace, and the layer temperature control furnace is set with a protective atmosphere, which includes 20%-30% hydrogen and the rest is nitrogen.

Citation Information

Patent Citations

  • Copper-aluminum composite material, preparation process, flexible connecting piece and battery module

    CN117525760A

  • Preparation method of low-cost efficient antibacterial copper-containing titanium alloy plate

    CN117548676A